Direct Two-Photon Excitation of Isomeric Transition in Thorium-229 Nucleus - Romanenko, V.I.; Udovitskaya, Ye.G.; Yatsenko, L.P.; Romanenko, A.V.; Litvinov, A.N.; Kazakov, G.A. (Ukrainian Journal of Physics, 2021)
A possibility of the two-photon excitation of an isomeric state in a nucleus of thorium-229 has been discussed. The fluorescence intensity of the excitation is demonstrated to be identical for the irradiation of nuclei with either monochromatic light or polychromatic radiation consisting of a sequence of short light pulses of the same intensity. The two-photon excitation of Th3+ ion in an electromagnetic trap with a focused laser beam with a wavelength of about 320 nm and power of 100 mW can lead to the absorption saturation, at which the fluorescence emission with the frequency of the transition in a nucleus is maximal. In crystals doped with Th4+ to a concentration of about 1018 cm-3 and irradiated with a laser radiation 10 W in power, the emission of several photons per second with a wavelength of about 160 nm becomes possible.